PENDIDIKAN MULTIKULTURAL DALAM BINGKAI ISLAM NUSANTARA PERSPEKTIF KH. SAID AQIL SIROJ - Hasan Baharun; Farah Nuril Badriyah (Tafáqquh: Jurnal Penelitian Dan Kajian Keislaman, 2020)
This study aims to analyze the thinking of KH. Said Aqil Siroj about multicultural education in the frame of Islam Nusantara, where KH. Said Aqil Siroj is a phenomenal figure in the community, and has an open mind to the dynamics of differences in Indonesia. This study uses a qualitative approach with library research, in which researchers attempt to collect data derived from books, scientific journals, speeches and statements of KH. Said Aqil Siroj in various media, both print and electronic media, and other documents. The data analysis technique uses content analysis. The results showed that; multicultural education in the frame of Islam Nusantara Islam, according to KH. Said Aqil Siroj can be implemented in a way; mobilize and optimize the role of Kiai in the community, strengthen the curriculum in Islamic educational institutions based on multiculturalism, carry out regeneration to strengthen organizational solidarity, and instill and teach the attitude of nationalism to the community